ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI PETANI TEBU DI KENAGARIAN BUKIK BATABUAH AGAM - Annisa, Indah Febri (Universitas Muhammadiyah Sidenreng Rappang, 2021)
This research aims to examine the level of motivation of sugar cane farmers and to analyze the correlation between internal and external factors with the farmer’s motivation. The research has been carried out from January until February 2016 by using survey method with simple random sampling, and 30 processing farmers. The economic motivation of the farmers as low (53,34%), motivation of affiliates catagorized as medium category which is 53.33% and the level of achievement as medium category (40%). The research finds that there was no significantly correlation between age, formal education, household income, participation in farmers groups, and the courage of taking risks with the motivation of farmers. The suggested is (1) provide training for new skills in terms of processing sugar cane for higher economic value. (2) higer the participate in farmer group activities.